Nutritional status in multi-drug resistance-pulmonary tuberculosis patients - Kumar, Amit; Kakkar, Rakesh; Kandpal, S D; Sindhwani, Girish (Indian Journal of Community Health, 2014)
Introduction: Malnutrition and tuberculosis are the major concerns of underdeveloped regions of the world. Undernutrition increases the risk of tuberculosis (TB) and in turn TB can lead to Malnutrition. Undernutrition is therefore highly prevalent among people with TB. It has been demonstrated that undernutrition is a risk factor for progression from TB infection to active TB disease and severe form viz. MDR-TB. Undernutrition is a predictor of increased risk of death and TB relapse. Objectives: To study the effect of nutrition in MDR-TB patients at DR-TB centre, Dehradun. Methodology: The Observational cross sectional study was conducted at Drug Resistant Tuberculosis (DR-TB) Centre of HIMS, Dehradun over a period of 12 months to include all the cases reported from 1st October, 2011 (start of DR-TB Centre at HIMS, Dehradun) to 30th April, 2014. 376 Subjects were recruited from 1598 suspected MDR TB subjects who were screened by Drug Susceptibility Testing (DST) results. Results: Out of 376 MDR-TB patients, 258 (68.6%) subjects were found to be undernourished. The mean body mass index (BMI) was 17.33+1.99 kg/m2. Though undernutrition was more common among Males (61.2%) but female’s BMI was more affected by MDR in comparison to males. Treatment success was better amongst males between 21- 60 year age group with normal BMI having mono drug resistance with no adverse reaction. The majority 47 (18.2%) of adverse effect was found in undernourished patients. Treatment outcome was also poor among undernourished (76.9%) MDR-TB patients. Conclusion: Prevalence of undernutrition was high (68.6%) among subjects and the mean BMI was lower in female. Adverse drug reaction, poor treatment outcome are attributes of Undernutrition.